Evaluation of Academic Self - Efficacy Perceptions and Instructional Dissent Attitudes of Teacher Candidates in Terms of Classroom Management - Yıldırım, Remzi; Özen, Hamit (Asian Journal of Education and Training, 2019)
In this study, academic self-efficacy perceptions and instructional dissent attitudes of teacher candidates have been examined and the findings have been evaluated in terms of classroom management. The population consists 2409 teacher candidates from the Faculty of Education in Eskisehir Osman Gazi University in the fall semester of 2018. Descriptive statistics were used while evaluating their perceptions and attitudes. Non-parametric tests were applied in the analysis since the data distribution was not normal. Mann Whitney U Analysis was used to determine whether there was a significant difference in their academic self-efficacy perceptions and instructional dissent attitudes by gender, while Kruskal Wallis Analysis was used to determine whether there was a significant difference by departments. Spearman’s Rank Correlation Analysis was used to determine whether there is a relationship between their academic self-efficacy perceptions and instructional dissent attitudes. According to the findings, it has been seen that the academic self-efficacy perceptions of teacher candidates are at a normal level and instructional dissent attitudes are at a low level. The total scores of teacher candidates calculated for the whole academic self-efficacy perceptions and coping subdimension were significantly different in favor of female candidates. There was no significant difference by departments. There was no significant difference in instructional dissent by gender and departments. It has been found out that there is a low-level relationship between the total scores of academic self-efficacy perception levels and instructional dissent attitudes of teacher candidates.